THE ROLE OF GERMAN ENTREPRENEURS IN THE ECONOMIC DEVELOPMENT OF THE REGION (Scientific journal of the Fergana State University, 2023)
This article describes the historical significance of the activities of German entrepreneurs for the economic development of the city of Kokand in the 19th century. The article presents the historical facts of the money turnover of the banks of the city of Kokand. For the first time in the country, such terms as credit, installment were used. The conditions of residence and the type of activity of these entrepreneurs are described in more detail. The reasons for the closure of some enterprises at that time were investigated.